Study on the Preparation and Properties of Inorganic Silica Single-Layer Film - Li, Haihong; Zhao, Qinyi; Wang, Guangzhen; Xu, Yanbei; Liu, Ke; Hu, Leyong (Asian Journal of Chemistry, 2015)
The silica single-layer film catalyzed by hydrochloric acid was prepared on the glass matrix with tetraethyl orthosilicate and absolute alcohol as main raw materials by sol-gel method. The reaction mechanism of sol-gel method included hydrolysis reactions and polymerization reactions. The samples were characterized by visible spectrophotometer, X-ray diffraction and thermal analysis (TG and DTA). Results showed that the light transmittance of the silica single-layer film was enhanced remarkably. X-ray diffraction results indicated that the single-layer film possessed amorphous characteristic. Adhesion tests showed that the adhesion force between the silica single-layer film and the glass matrix was very strong. Thermal analytical results demonstrated that silica would absorb heat when it transformed from amorphous structure to crystal structure.